Trying Lubet's ethnography: On methodology, writing, and ethics - Yanow, Dvora (Politics, groups & identities, 2021)
By the early 2000s, immersed in fieldwork methods literatures (participant-observer ethnography, interviewing, and document-based research), I increasingly saw that “evidence” meant something different in different research and professional practices. Its operational meanings in law and journalism especially interested me. During a sabbatical at UC Berkeley’s Center for the Study of Law and Society, I audited the Law School’s evidence course. The terrain was familiar, then, as I read Steven Lubet’s Interrogating Ethnography (2018).Lubet zeroes in on a single tranche of ethnographic research: “primarily” (1) urban ethnographies (2) in US settings (3) by sociologists (2018, xiii). Crucially, however, the book’s language does not contain the critique within these parameters, generalizing to ethnography entire, holding it to the requirements of a courtroom’s evidentiary practices, and extending prior criticisms of another book and its reception. Consider the title. It is not Interrogating US Urban Ethnography – Seeing like a Sociologist. “Ethnography” remains unmarked throughout, enabling the generalization. Many of its criticisms concern ethnographers’ claims advanced – it is argued – in the absence of (clear) evidence (of the sort admissible in a court of law). Ironically, the book often advances its own claims through the strategic use of rhetorical devices rather than empirical evidence. Indeed, while critiquing certain scholars for engaging topics without possessing requisite knowledge, Lubet does the same, especially concerning methodology and research ethics.No scholar would reasonably be expected to cover ethnography’s entire range. But a scholar should be held to account for generalizing beyond stipulated parameters – especially when a reader might not remember the domain established on page xiii and think the attributed faults characterize all ethnographies. Moreover, the inconsistencies between the expectations of others’ research and the actualities of the book’s own writing undermine the critique. I explore two aspects of the domain-setting before turning to the writing.